Prevalence of suboccipital and intradural vertebral artery variants: a systematic review with meta-analysis. - Triantafyllou, George; Papadopoulos-Manoralarakis, Panagiotis; Tudose, Rǎzvan Costin; Rusu, Mugurel Constantin; Tsakotos, George; Piagkou, Maria (Neuroradiology, 2025)
Purpose: The current systematic review, along with a meta-analysis, aims to present and calculate the pooled prevalence of the morphological variants of the vertebral artery (VA) within the suboccipital (V3) and intradural (V4) segments. Methods: According to the most recent guidelines, the systematic review was conducted using four online databases. Eligible studies were extracted, and a meta-analysis was performed utilizing R programming software. A subgroup analysis was conducted based on nationality and imaging techniques. Results: The systematic review revealed thirty-two (32) studies involving 176,391 patients. The pooled prevalence of VA fenestration was established at 0.30% (95% CI: 0.14–0.51). Furthermore, the persistent first intersegmental artery (PFIA) was estimated to have a pooled prevalence of 1.17% (95% CI: 0.36–2.34), wherein the imaging technique and nationality served as a significant moderator. An aberrant origin of the posterior inferior cerebellar artery from the V3 segment was identified, with a pooled prevalence of 2.69% (95% CI: 1.13–4.82). Additionally, the pooled VA dominance, hypoplasia, and atresia prevalences were recorded at 27.45%, 13.41%, and 5.39%, respectively. Conclusions: Magnetic resonance or computed tomography angiographies can accurately illustrate the distal VA's diverse anatomical configurations. Specific variants hold substantial clinical significance, as they are correlated with posterior circulation cerebrovascular incidents and may complicate posterior approaches to the craniocervical region.